God and Divinity (Analysis of Surah Al-Baqarah 165 and Surah Al-Ikhlas) - Rizki Nazriel Himawan; Tri Amelia Maharani; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In the Qur’an, the Oneness of Allah can be proven in three main parts, namely: the reality of visible form, the feelings found in the human soul, and logical postulates. In this paper, the researcher focuses on the perspective of the Al-Qur'an Surah Al-ikhlas and Surah Al-Baqarah verse 165. This research aims to show that Islam is a religion that truly adheres to pure monotheism. The understanding of the Oneness of God, according to religions other than Islam, can be said to be a confession of Oneness, but it is not pure. This is because they still recognize Ilah-ilah (Gods). This research includes qualitative research. The method used in this paper is the descriptive analysis method, namely a method that describes and analyzes a problem. The material object of this study is knowledge about God, and philosophy is the formal object. The literature sources used are books, e-books, journals, articles and trusted websites. Literary sources are collected using search engines and through libraries. The literature sources are then analyzed and concluded, the results of the literature study are put into a systematic narrative form by citing and referring to literature sources. The writing format is adjusted to applicable scientific principles and guidelines. The result of this research is that the concept of the Almighty Godhead, according to human thought, is different from the concept of the Almighty Godhead according to Islamic teachings. Everything in the universe was created by the Almighty Creator (Khalik). Humans who are given reason, when they pay attention to natural symptoms and phenomena, will come to the conclusion that this amazing nature must have been created by the Almighty. Logical reason also understands that what is created is not the same as the Creator. Creatures, apart from those that are real and can be known with the five senses, there are also those that are immaterial and cannot be reached by the human senses.